The COVID-19 pandemic and firms' e-learning use: Implications for inequality in training opportunities - Christoph Müller (Journal for Labour Market Research, 2024)
This paper investigates whether the adoption of E-learning by firms contributed to offset the decrease in firm-sponsored training during the COVID-19 pandemic. Using a novel firm level survey linked with administrative data on the universe of workers within those firms, I study the role of E-learning in firms' training activities during the crisis. I find that the COVID-19 pandemic substantially decreased firm-sponsored training by up to 11 percentage points. However, firms' ability to use E-learning nullifies this negative effect. Furthermore, the differential capabilities of firms to apply E-learning might exacerbate already prevalent inequalities in training opportunities.
Keywords: D23; I24; L23; 330; COVID-19 pandemic; Inequality in firm-financed training; Labor market inequality